2014
DOI: 10.1007/s13197-013-1233-2
|View full text |Cite
|
Sign up to set email alerts
|

Alternative fat substitutes for beef burger: technological and sensory characteristics

Abstract: This study aimed to develop a type of hamburger meat product and evaluate the physical features and sensory formulations of oatmeal flour, flour of green banana pulp, flour of green banana peel, flour of apple peel and pulp of Green Banana as fat substitutes. Regarding color, the formulations containing fat substitutes based on green banana presented lower values for b* and L*. Hamburgers with added oatmeal and apple peel flour obtained high values of a* and low values of L*, producing the reddest burgers. Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
34
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 35 publications
10
34
1
3
Order By: Relevance
“…Low and positive values of a* and b* represent a low setting to red and yellow dyes, respectively. Such characteristics were also observed in other studies (Bastos et al, 2014;López-Vargas et al, 2014;Ramadhan et al, 2011).…”
Section: Physicochemical Properties Of Cooked Beef Burgerssupporting
confidence: 87%
“…Low and positive values of a* and b* represent a low setting to red and yellow dyes, respectively. Such characteristics were also observed in other studies (Bastos et al, 2014;López-Vargas et al, 2014;Ramadhan et al, 2011).…”
Section: Physicochemical Properties Of Cooked Beef Burgerssupporting
confidence: 87%
“…Tie Su et al (2013) report that the creamy colour of okara, similar to that of fat from beef, contributes to lower luminosity in the formulations without okara. Bastos et al (2014) found similar results when they were researching hamburgers containing fat substitutes. Luminosity decreased along the storage period in all treatments, except for fried F1 and F2 where there was no difference during the storage period.…”
Section: Physical Analysessupporting
confidence: 53%
“…Novel food ingredients and structuring approaches are required to fabricate this kind of reduced-calorie product without adversely affecting desirable quality attributes (Pereira et al, 2015). There has been particular interest in the utilization of dietary fibers and proteins as functional ingredients to create these kinds of products due to their perceived healthfulness (Bastos et al, 2014;Harrold et al, 2014;Lluch et al, 2010;Peker and Arslan, 2013). Proteins and dietary fibers can be assembled into hydrogel particles using food design approaches that may be used to modulate food texture and appearance, and therefore create novel reduced calorie foods.…”
Section: Introductionmentioning
confidence: 99%